A study of corrosion on electrodeposited superhydrophobic copper surfaces. (1st July 2021) - Mousavi, S.M.A; Pitchumani, R.
Highlights: Presents a facile, low energy, electrodepostion method for fabrication of copper-based superhydrophobic surfaces. Presents, for the first time, a systematic study on the effect of surface functionalization time. Presents the corrosion inhibition characteristics of superhydrophobic surfaces in a wide range of corrosive environments. Reports corrosion resistance of superhydrophobic copper surfaces, for the first time, as a function of temperature. Presents a study of corrosion durability of the surfaces under long-term immersion in the corrosive environments. Abstract: This study considers the corrosion characteristics of superhydrophobic copper surfaces with multiscale asperities formed inherently on a copper substrate, using a facile, low energy, electrodepostion method. A systematic study is presented for the first time on the effect of surface functionalization time on long-term immersion in a wide range of corrosive environments from the extremely acidic to the extremely alkaline. The corrosion resistance is also reported for the first time as a function of temperature in the range 23–85 °C. The superhydrophobic surfaces are shown to enhance corrosion resistance by up to four orders of magnitude compared to bare copper.